Microstructure characterization of IG110 and reactor pebble graphite using synchrotron micro X‐ray diffraction 2D maps. (23rd September 2020) - He, Zhoutong; Zhang, Can; Tang, Hui; Liu, Ming; Marsden, Barry J.; Zhou, Xingtai
Abstract : Knowledge about the microstructure of nuclear graphite is critical to the understanding of its irradiation behavior in the reactor. Using micro X‐ray diffraction (μXRD) two‐dimensional (2D) maps, the crystallite character of IG110 and reactor pebble graphite was characterized at the submillimeter range with a spatial resolution of about 5 μm. Various structures in the nuclear graphite were identified by comparing the X‐ray diffraction peak intensity, position, and full width at half maximum (FWHM) 2D maps. The two‐peak feature of the FWHM histograms seen in pebble graphite may be related to the raw coke and natural graphite used as raw materials. With these results, it can be concluded that the μXRD 2D map is an effective method to characterize the microstructure of nuclear graphite.